Volunteers in public schools - National Research Council (U.S.). Committee on the Use of Volunteers in Schools; Michael, Bernard (Washington, D.C. : National Academy Press, 1990)
Offers an overview of volunteer activity in US public schools - reporting on how volunteers are being used in schools, what factors make programs successful, what research will enhance our ability to create good programs, and what directions our national policy should take.
Introduction -- Development of organized school volunteerism in the United States -- School volunteers: a statistical profile -- Review of research and evaluation literature on school volunteerism -- Some exemplary volunteer programs: Ann Arbor, Michigan ; Boston, Massachusetts ; Chicago, Illinois ; Contra Costa County, California ; Corsicana, Texas ; Dade County, Florida ; Dallas, Texas ; Kingfield, Maine ; Montgomery County, Maryland ; San Fernando Valley, California ; San Francisco, California ; Tulsa, Oklahoma ; Washington, D.C. -- Factors in school volunteerism -- A call to action -- Appendixes: Data from NCES schools and staffing survey, 1987-1988 ; Annotated bibliography ; Biographical sketches of committee members and staff.
Includes bibliographical references (pages 121-143).
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Volunteer workers in education -- United States; Volunteer workers in education -- United States -- Statistics; Volunteer workers in education; Bénévoles en éducation.; Bénévoles en éducation -- États-Unis.; Bénévoles en éducation -- États-Unis -- Statistiques; EDUCATION -- Administration -- General; Volunteer workers in education; United States; Schule; Volontär; USA; Statistics